The minimum transforming region of v-abl is the segment encoding protein-tyrosine kinase. - Prywes, R (1985)
Only 1.2 kilobases (kb) at the 5' end of the 3.9-kb v-abl sequence in Abelson murine leukemia virus is required for fibroblast transformation. A precise delineation of this minimum transforming region was made by using small 5' or 3' deletions. Insertions of four amino acids, generated by putting synthetic DNA linkers into various restriction enzyme cleavage sites, abolished transforming activity, indicating that much of the internal sequence of the minimum transforming region plays a critical role in the transformation process. This 5' 1.2 kb of v-abl encodes protein-tyrosine kinase activity when expressed in Escherichia coli. Each of the mutations which caused a loss of transformation activity also resulted in a loss of protein-tyrosine kinase activity when expressed in E. coli. The minimum transforming region of v-abl contains amino acid homology to other protein-tyrosine kinase oncogenes, and a comparison with these oncogenes is presented.